The Nigerian economy : issues and problems of management - Iyanda,Olakunle (Lagos : Malthouse, 1987)
The paper addresses the problem created by an inappropriate industrial policy and the constraints inhibiting the accomplishment of st objectives
Includes index.
obn 23/01/2019
Loans
Keywords: Nigeria-Economic policy; Management--Nigeria.; Economic policy